S1_3_StopEarthRotation - Walji, Sherali; Feetham, Luke; Holden, Josef; Gray, David (Physics Special Topics, 2009)
It has been stated in the past by Dr. (h.c.). Â Jeremy Clarkson that a car could have enough torque that it would send the Earth spinning backwards rather then the car being propelled forwards. Â Using simple calculations it can be shown that this is impossible.